2016
DOI: 10.1177/1555412016647848
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Violence in Contemporary Game Design

Abstract: Through a textual analysis of three noted examples-Bioshock, Spec Ops: The Line, and Grand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…However, by depending on comparisons with media forms that are generically different, they fall prey to a logical fallacy that subjects one media form to the limitations of another. Even though “gameplay systems are no less [or more] suffused with meaning than the more explicitly rhetorical dimensions of narrative and representation” (Maloney, 2019, p. 33), the active ludology against passive cinematic reception debate seems to be “a comparison of apples and oranges”—it depends on a false binary between the two without duly considering different and subjective definitions of “activity,” nor the differing vehicles and generic resources through which horror is created.…”
Section: Conclusion—taxonomy Over Binarymentioning
confidence: 99%
“…However, by depending on comparisons with media forms that are generically different, they fall prey to a logical fallacy that subjects one media form to the limitations of another. Even though “gameplay systems are no less [or more] suffused with meaning than the more explicitly rhetorical dimensions of narrative and representation” (Maloney, 2019, p. 33), the active ludology against passive cinematic reception debate seems to be “a comparison of apples and oranges”—it depends on a false binary between the two without duly considering different and subjective definitions of “activity,” nor the differing vehicles and generic resources through which horror is created.…”
Section: Conclusion—taxonomy Over Binarymentioning
confidence: 99%
“…With that in mind, in researching this sort of interaction before the advent of video games, Huizinga (1949:46) found that 'culture arises in the form of play, it is played from the very beginning', giving levity to Rodgers' (2016:1302) claim that researching games tells us something about our culture. Directly addressing GTAV through a textual analysis, Maloney (2016) finds that rewarding players for acts of subjective violence furthers a sort of 'ambivalence' where violence becomes normalised. But he also calls upon an ambient ambivalence of narrative that embeds violence implicitly into the background of gameplay -systemic violences can be found in elements of gaming as straightforward as competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La fantasía de poder es un concepto del que se ha hablado en algunas investigaciones previas sobre videojuegos. Marcus Maloney (2016), por ejemplo, escribe un artículo en el que analiza cómo se desarrolla y va evolucionando la fantasía de poder en videojuegos como Bioshock o Grand Theft Auto V. El autor clasifica y compara las dinámicas violentas entre estos videojuegos y asegura que existen algunas cargas violentas más débiles y otras más fuertes, siendo así las más fuertes las que más complacen a lxs jugadorxs. De esta forma, Maloney (2016) asegura que las cargas violentas más fuertes se relacionan con paradigmas de poder que se ven activados cuando lxs jugadorxs sienten que tienen el dominio sobre el curso del juego.…”
Section: Análisis Socio-digital Deunclassified